Vesalius: high‐resolution in silico anatomization of spatial transcriptomic data using image analysis. Issue 9 (6th September 2022) - Martin, Patrick C N; Kim, Hyobin; Lövkvist, Cecilia; Hong, Byung‐Woo; Won, Kyoung Jae
Abstract: Characterization of tissue architecture promises to deliver insights into development, cell communication, and disease. In silico spatial domain retrieval methods have been developed for spatial transcriptomics (ST) data assuming transcriptional similarity of neighboring barcodes. However, domain retrieval approaches with this assumption cannot work in complex tissues composed of multiple cell types. This task becomes especially challenging in cellular resolution ST methods. We developed Vesalius to decipher tissue anatomy from ST data by applying image processing technology. Vesalius uniquely detected territories composed of multiple cell types and successfully recovered tissue structures in high‐resolution ST data including in mouse brain, embryo, liver, and colon. Utilizing this tissue architecture, Vesalius identified tissue morphology‐specific gene expression and regional specific gene expression changes for astrocytes, interneuron, oligodendrocytes, and entorhinal cells in the mouse brain. Synopsis: Vesalius is a computational tool for recovering tissue territories from spatial transcriptomics data using image processing technology. Vesalius illustrates how uniform tissue territories can help understanding tissue heterogeneity. Vesalius leverages image analysis to investigate spatial transcriptomics data by embedding the transcriptome into RGB image arrays. Vesalius provides uniform tissue territories from high resolution spatial transcriptomics data. Downstream analysis of isolated tissue territories reveals the finer details of spatial patterning as well as tissue specific gene expression within cell types. Abstract : Vesalius is a computational tool for recovering tissue territories from spatial transcriptomics data using image processing technology. Vesalius illustrates how uniform tissue territories can help understanding tissue heterogeneity.